Educação e serviço social: elo para a construção da cidadania - Martins, Eliana Bolorino Canteiro (2007)
This thesis addresses the professional practice of social workers within the educational policy in cities in the State of São Paulo, demonstrating how they use the socio-occupational spaces generated by the current juridical orders guiding this policy. Since their origin, social policies express the conflicts coming from the interests of different social forces, at a certain socio-historical context. Education has a strategic position in both cultural and productive aspects; thus, the educational policy expresses, in its juridical basis, different political projects existing in a certain society. In this sense, interpretation of the juridical basis of the current Brazilian educational policy and the Statute of the Child and Adolescent reveals that there are spaces for social work intervention in three aspects: democratization of the process of education; rendering of assistance and socioeducational services; and the articulation of educational policy with other policies. The research screened 37 cities that have social workers working in all levels of basic education, namely infant education, elementary school and special education. Among these cities, 28 cities and 55 social workers participated in the present study by responding to the questionnaires. At the second stage, 6 social workers from 3 cities conducted focal interviews with a view to identify the following issues: professional profile; history of inclusion of Social Work in the field of education in each city; and the professional practice effectively occurring at these cities. The study revealed differences between the spaces existing according to the law and the utilization of such spaces by the social workers in their professional practice. It was noticed that the social workers act primarily on the relationship among school, family and society, with different perspectives for intervention. The relevance of the socio-educational influence of social workers within the education policy was also demonstrated contributing to uncover the reality, i.e., in the process of production and reproduction of the capitalist society, showing the origin of social inequalities. Analysis of the current Social Work practice within the educational policy presented in this thesis aims to enlarge and qualify this practice, enriching the education in its different scopes, as being essential for the organization of culture to favor the interest of the majority of people. Considering that educational institutions are contradictory from a Gramscian perspective, i.e. they exert the ideology and counter ideology they represent important strategic spaces for the professional practice of Social Work, allowing the formation of human beings towards their emancipation